OPTIMIZATION OF YOUTUBE MEDIA TO INCREASE INTEREST IN LEARNING SKIING IN GRADE XI STUDENTS OF MA AL FATTAH SUNGAI BINJAI BUNGO - Maryatul Hikmah; Opi Teci Darisma; Mabruri (Al-Hijr: Journal of Adulearn World, 2026)
This research is motivated by the low interest of students in the subject of Islamic Cultural History (SKI) at the Al-Fattah Islamic Boarding School in Sungai Binjai, which has been dominated by lecture methods and the lack of varied learning media. This condition encourages the need to optimize digital media that is close to the character of the current generation, one of which is YouTube as an audio-visual media. This study aims to describe the use of YouTube media in SKI learning, identify its supporting and inhibiting factors, and analyze its influence on students’ learning interests. The approach used is qualitative with the type of field research and descriptive design at MA Al Fattah Sungai Binjai, with the subjects of SKI teachers, students, and related parties. Data is collected through observation, in-depth interviews, and documentation, then analyzed interactively through reduction, presentation, and conclusions drawn, with triangulation of sources and techniques to maintain validity. The results of the study show that YouTube is utilized through planning, implementation, and follow-up stages that are integrated with SKI learning objectives, supported by media characters, ease of access, and the role of teachers, but hampered by technical aspects and pedagogical readiness. The use of YouTube has a positive effect on students’ interest in learning through increased feelings of pleasure, attention, engagement, and self-learning initiatives. The novelty of the research lies in the focus of optimizing YouTube for SKI learning interests in the context of pesantren-based madrasah aliyah and its implications for the development of learning design and policy use of digital media in Islamic education.